Protective Effects of Chinese Traditional Medicine Buyang Huanwu Decoction on Myocardial Injury. (5th June 2011) - Yang, Guangde; Fang, Zhiyuan; Liu, Yu; Zhang, Hui; Shi, Xiaolian; Ji, Qiaoli; Lin, Qinqin; Lin, Rong
Abstract : Many clinical studies have reported that Buyang Huanwu Decoction (BYHWD) has a protective effect on ischemic heart disease (IHD). In the present study, the protective effect of BYHWD on myocardial ischemia was investigated. Different doses of BYHWD and Compound Danshen Dropping Pills (CDDP) were lavaged to rats, respectively, isoproterenol (ISO) was intraperitoneally injected in to all animals to induce myocardial ischemia except the control group. Electrocardiogram (ECG) of each animal was recorded; activities of lactate dehydrogenase (LDH), creatine kinase (CK) and aspartate aminotransferase (AST) in serum were detected. As the results of ECG showed, pre-treatment with BYHWD inhibited ischemic myocardial injury, and the activities of LDH, CK and AST were lower than those in the myocardial ischemia model group, which suggests that BYHWD rescues the myocardium from ischemia status. To research the potential mechanism, the level of nitric oxide (NO), nitric oxide syntheses (NOS) and inducible nitric oxide syntheses (iNOS), the expression of iNOS and ligand of cluster of differentiation 40 (CD40L) were detected. The results revealed that BYHWD significantly decreased the level of NO, NOS and iNOS in serum. Moreover, BYHWD decreased the expression of iNOS and CD40L in myocardial tissues. These results indicate that the protective effect of BYHWD on myocardial ischemia and mechanism are associated with inhibition of iNOS and CD40L expression.